Jews and Israel 2024: A Survey of Canadian Attitudes and Jewish Perceptions - Brym, Robert (Canadian Jewish Studies / Études juives canadiennes, 2024)
Most Canadian Jews feel unsafe and victimized. They perceive a rise in negative attitudes toward Jews in recent months and years. Most doubt the situation will improve. The main reason they feel this way is that extreme anti-Israel statements and actions have proliferated in recent months. Because support for the existence of a Jewish state in Israel is a central component of their identity, most Jews regard extreme anti-Israel statements and actions as a threat to their existence as Jews. Most non-Jewish Canadians do not have negative toward Jews. However, non-Jewish university students, Quebecois, and especially Muslim Canadians tend to have significantly more negative attitudes towards Jews than does the non-Jewish population as a whole. Non-Jewish Canadians’ attitudes toward Israel tend to be significantly more negative than their attitudes toward Jews. The groups with the most negative attitudes toward Israel are, in order, Muslims, non-Jewish supporters of the New Democratic Party, and non-Jewish university students. Among non-Jewish Canadians, the correlation between attitudes toward Jews and attitudes toward Israel is positive, statistically significant, and at the low end of moderate. This means that, although some critics of Israel have negative attitudes toward Jews, most do not. Exceptions include Muslims, who tend to score relatively high on negative attitudes toward Jews and Israel; and people who identify as hard right, supporters of the Conservative and People’s Parties, and Canadians over the age of sixty-four, who tend to score relatively low on negative attitudes toward Jews and Israel. On the whole, Canadian Jews have experienced a reduction in their emotional attachment to Israel because of the Israel-Hamas war and the rightward drift of Israeli government policy. The trends just listed are derived from a survey conducted between 1 and 28 February 2024. The survey was based on four broadly representative independent samples of Canadian residents: 1,121 non-Jewish adults, 1,010 non-Jewish university students, 312 Muslim adults, and 414 Jewish adults, for a total of 2,857 respondents. In addition to providing an analysis of the survey results for the educated non-specialist public, this report seeks to place its findings in social context and in the context of prior survey research on attitudes toward Jews and Israel.